The theses for MD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
O.I. Malomuzh – Chronic liver diseases: indications and optimal terms for transplantation.Ye.V. Stepanova – Clinical and genetic aspects of a Crohn’s disease.